Sex and Species Differences in the Development of Diet-Induced Obesity and Metabolic Disturbances in Rodents - Maric, Ivana; Krieger, Jean-Philippe; van der Velden, Pauline; Börchers, Stina; Asker, Mohammed; Vujicic, Milica; Wernstedt Asterholm, Ingrid; Skibicka, Karolina P. (Frontiers in Nutrition, 2022)
Prevalence and health consequences of obesity differ between men and women. Yet, most preclinical studies investigating the etiology of obesity have, to date, been conducted in male rodents. Notably, diet is a major determinant of obesity, but sex differences in rodent models of diet-induced obesity, and the mechanisms that underlie such differences, are still understudied. Here, we aim to determine whether time course and characteristics of diet-induced obesity differ between sexes in rats and mice, and to investigate the potential causes of the observed divergence. To achieve this, we offered the most commonly tested rodents of both sexes, SD rats and C57BL6 mice, a free choice of 60 % high fat diet (HFD) and regular chow; body weight, food intake, fat mass, brown adipose responses, locomotor activity and glucose tolerance were assessed in a similar manner in both species. Our results indicate that overall diet-induced hyperphagia is greater in males but that females display a higher preference for the HFD, irrespective of species. Female rats, compared to males, showed a delay in diet-induced weight gain and less metabolic complications. Although male rats increased brown adipose tissue thermogenesis in response to the HFD challenge, this was not sufficient to counteract increased adiposity. In contrast to rats, female and male mice presented with a dramatic adiposity and impaired glucose tolerance, and a decreased energy expenditure. Female mice showed a 5-fold increase in visceral fat, compared to 2-fold increase seen in male mice. Overall, we found that male and female rodents responded very differently to HFD challenge, and engaged different compensatory energy expenditure mechanisms. In addition, these sex differences are divergent in rats and mice. We conclude that SD rats have a better face validity for the lower prevalence of overweight in women, while C57BL6 mice may better model the increased prevalence of morbid obesity in women.